Penyuluhan Pencegahan Tindakan Kekerasan Seksual Pada Anak di SD Negeri Babakan - Mufadilatul Ulya; Widad Mukharrirotul Fiqih; Dewi Mutaena; Fatin Farhana; Muhammad Izzu Rochman; Dian Rif'iyati (Universitas Maritim AMNI Semarang, 2023)
Child abuse often occurs in today's digital era, even sexual harassment has become a frightening thought for Indonesian children today. This activity aims to help students to find out what efforts can be made in order to prevent and avoid the occurrence of sexual violence against themselves. The methods and media used in this activity are in the form of counseling using learning aids in the form of a PPT (Power Point) display which is made as attractive as possible to make it more effective and also uses video. The results show that many students still do not know about acts of sexual violence, with this counseling SD Negeri Babakan students can gain and increase their understanding of acts of sexual violence and what steps need to be taken if these acts occur to themselves. Through this counseling method students can easily understand acts of sexual violence and the efforts that need to be made to avoid it.